Sistem Pengelolaan Terbitan Berseri di UPT Perpustakaan Proklamator Bung Hatta Bukittinggi - Rahmadanela, Rahmadanela; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this paper is to describe (1) find out the serial publications management system in UPT Library Proclaimer Bung Hatta Bukittinggi, (2) know the obstacles faced in the serial issue management system in UPT Library Proclaimer Bung Hatta Bukittinggi. The Data collected through observations, interviews and literature study. The findings of this research is based on analysing school financing data can be concluded as follows: (1) The management of serial issues that were on PPBH Bukittinggi consisting of five activities which were Procurement, processing, service issues resplendent, preservation issues resplendent, and promotion issues splendent (2) obstacles faced was the lack of cooperation of libraries with the Publisher, the absence of cataloge and index, the Ministry has not gone well, tools for menjilid much less, and there hasn't been done in a series of promotional publications. Keywords: management of publications series